Glycemic control and fetal abdominal circumference - S Gopinath; G Varalakshmi; K Manoj; Rubiya (Indian Journal of Endocrinology and Metabolism, 2012)
Aim: To study about the correlation between the glycemic status and increase in fetal abdominal circumference in gestational diabetes patients and its relationship with fetal birth weight. Materials and Methods: Seventy-five gestational diabetes mellitus (GDM) patients were taken up for study with duly informed consent and suggested for anthropometry profile and glycemic profile with HbA1C. Fetal abdominal circumference was measured during routine scans. The patients were followed up till delivery and the fetal birth was noted. Inclusion Criteria: Seventy-five gestational diabetic mothers who have attended a secondary level diabetic clinic and on regular follow-up were included in the study. Exclusion Criteria: Pre-GDM mothers, patients with co-morbid disease were excluded from the study. Expected Results: Fetal abdominal circumference correlated well with fluctuating glycemic control and fetal birth weight.